Home Environmental Factors Associated with Falls Among Elderly in Ubon Ratchathani, Thailand [Letter] - Song J; Wang S (Journal of Multidisciplinary Healthcare, 2024)
Jing Song,1 Song Wang2 1Bengbu Medical University, Bengbu, Anhui, People’s Republic of China; 2West China School of Nursing/West China Hospital, Sichuan University, Chengdu, Sichuan, People’s Republic of ChinaCorrespondence: Song Wang, West China School of Nursing/West China Hospital, Sichuan University, No. 37, Guoxue Alley, Wuhou District, Chengdu, Sichuan, 610041, People’s Republic of China, Email wangzhikang2018@126.com